The impact of market orientation and strategic HRM on firm performance: the case of Chinese enterprises - Wei, Li-Qun; Lau, Chung-Ming (Journal of International Business Studies, 2008)
This study examines market orientation as the antecedent to strategic human resource management (SHRM), and the related effects on firm performance in an emerging economy context. It is suggested that the relationship between SHRM and firm performance is moderated by ownership type and autonomy in staffing of these firms. Empirical results from a sample of Chinese firms from various industries and regions reveal that SHRM mediates the relationship between market orientation and firm performance. It is also found that the effect of SHRM on firm performance is stronger for firms with a higher degree of autonomy in staffing, and weaker for private firms. Other types of ownership (state or foreign) have no effect on this relationship.